Energy harvesting feasibility from photovoltaic/thermal (PV/T) hybrid system with Ag/Cr2O3-glycerol nanofluid optical filter. (October 2022) - Hashemian, Mehran; Jafarmadar, Samad; Khalilarya, Shahram; Faraji, Masoud
Abstract: In this interdisciplinary experimental study a new nanofluid-based optical filter (NFOF) was designed and tested for a photovoltaic/thermal (PV/T) hybrid system. To this end, Ag/ C r 2 O 3 nanoparticles (NPs) were synthesized with 5% concentration of Ag, then the obtained A g / C r 2 O 3 NPs were suspended in glycerol (C3 H8 O3 ). The prepared nanofluid optical filter is outstanding and novel from some aspects: (i) the simple synthesis method of A g / C r 2 O 3 NPs, (ii) bears desirable transmittance, (iii) high stability of nanoparticles in base fluid, (iv) low-cost production process, (v) acceptable overall energetic and exergetic efficiency. The intense solar irradiance occurs in the visible spectrum range where most solar systems are designed based on this range. Moreover, the highest spectral response of the silicon type solar cells can be achieved in wavelengths between 650 nm and 1075 nm (ideal window). Therefore, the prepared NFOF filters was designed to have maximum transmittance in wavelengths between 650 nm and 1075 nm for efficient photo-electrical conversion. Accordingly, they should have high absorbance in the wavelengths out of the said region (especially visible spectrum) for optimum photo-thermal conversion. The incident of spectra out of ideal window not only doesn't have any contribution to PV cell electricity generation, but also increases cell temperature which subsequently reduces its efficiency and longevity. For this purpose, NFOF was used as a selective thermal absorber that protects PV cell against unrequired spectra. Three different concentrations of A g / C r 2 O 3 NPs were suspended in glycerol (10 ppm, 40 ppm, and 80 ppm). The performance of the hybrid PV/T system was checked by photothermal/electrical conversion efficiency, merit function, and overall exergy efficiency. The maximum photothermal energy conversion efficiency is 31.55% which is obtained by Ag/Cr2 O3 -glycerol (80 ppm) NFOF. Also, the highest value of photoelectric energy conversion is 13.25% which is obtained when there is no filter. Moreover, the Ag/Cr2 O3 -glycerol (40 ppm) NFOF caused the highest amount of overall energy efficiency (41%) and merit function (1.558). When E(λ)≠0, the highest and lowest overall exergy efficiency during 30 min testing was obtained by glycerol and Ag/Cr2 O3 -glycerol (80 ppm), while this is completely inverse when E(λ) = 0. Graphical abstract: Image 1